Avaliação clínico-patológica cutânea de cães com leishmaniose visceral tratados com miltefosina e alopurinol - Freitas, Maria Sabrina de (2024)
Visceral leishmaniasis is a zoonosis with thousands of new cases annually worldwide. In some countries, including Brazil, it is a serious public health problem. The dog, the main reservoir, maintains the endemicity of VL in the urban environment due to its proximity to humans and the high cutaneous parasite load. The skin plays an important role in the immunopathogenesis of the disease, as it is the first organ infected by the parasite, in addition, due to the dermatotropic aspect of L. infantum, there is a high parasite load, facilitating infectivity to the vector. In view of the above, this study aimed to evaluate the clinical and histopathological findings and the parasite load of the skin of dogs with visceral leishmaniasis treated with miltefosine associated with allopurinol. Seventeen dogs were evaluated before and after 150 days of the beginning of treatment, submitted to collection of skin, blood and urine samples to establish the clinical score and describe the dermatological clinical findings and histopathological aspects, in addition to quantifying the skin parasite load by qPCR. After treatment, a reduction in the clinical score and laboratory abnormalities was observed, with remission of some clinical signs and normality of the mean values of hemoglobin, hematocrit and albumin/globulin ratio. The main skin changes initially observed were alopecia/hypotrichosis, ulcerative dermatitis, exfoliative dermatitis, and nasodigital hyperkeratosis. After treatment, there was a reduction in macroscopic lesions and a decrease in inflammation, with a predominance of macrophages in the inflammatory infiltrate, in addition, there was a significant reduction in the parasite load in all dogs. Miltefosine in association with allopurinol promoted clinical improvement, decreased clinical score, reduced parasite load, and improved skin inflammation in dogs after 150 days of treatment.